Word and Mystery: The Acoustics of Cultural Transmission During the Protestant Reformation - Boren, Braxton (Frontiers in Psychology, 2021)
To a first-order approximation we can place most worship services on a continuum between clarity and mystery, depending on the setting and content of the service. This liturgical space can be thought of as a combination of the physical acoustics of the worship space and the qualities of the sound created during the worship service. A very clear acoustic channel emphasizes semantic content, especially speech intelligibility. An immersive, reverberant acoustic emphasizes mystery and music. One of the chief challenges in acoustical design is the fact that both clarity and immersion are subjectively preferred by audiences, yet these two goals are almost mutually exclusive of one another. The movement along this continuum in liturgical space can also be seen in the religious contexts for many of the worship spaces constructed in the West in the last two millennia. In the case of religious ceremony, a free field acoustic environment provides more clarity and precision in the spoken word received from God and given to the congregation. Yet a diffuse field environment provides an embodied, otherworldly sense of the supernatural: the mystery of the faith received which cannot merely be put into words. This tension is perceptible in many of the religious controversies in the West during this time period. This article examines the history of the spaces used by early Western Catholic Christians as well as those of the traditions -- Lutheran and Calvinist -- that left the Catholic faith during the 16th century Reformation. By considering the stated goals of these traditions alongside the architectural and liturgical innovations they created, it can be seen that emergent liturgical spaces mirror the assumptions of their respective traditions regarding the proper balance between semantic and aesthetic communication during the worship service. The Reformed faiths' emphasis on the power of the Word is reflected in the liturgical space of their services, while the Catholic faith gave greater priority to the role of Mystery, in their liturgical space as well as their explicit theology. Once constructed, these spaces also aid the cultural transmission of the sung or spoken liturgy of each tradition to future generations.